2016
DOI: 10.1089/aid.2015.0110
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Transmitted Drug Resistance Mutations in Newly Diagnosed Antiretroviral-Naive Patients in Turkey

Abstract: HIV-1 replication is rapid and highly error-prone. Transmission of a drug-resistant HIV-1 strain is possible and occurs within the HIV-1-infected population. In this study, we aimed to determine the prevalence of transmitted drug resistance mutations (TDRMs) in 1,306 newly diagnosed untreated HIV-1-infected patients from 21 cities across six regions of Turkey between 2010 and 2015. TDRMs were identified according to the criteria provided by the World Health Organization's 2009 list of surveillance drug resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
0
14
0
3
Order By: Relevance
“…Furthermore, this indicates consistency with our previous studies. 12,13 However, there is a high level of heterogeneity in the HIV-1 diversity, specific geographic localization of Turkey may assist in explaining this phenomenon. Extraodinary mass…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this indicates consistency with our previous studies. 12,13 However, there is a high level of heterogeneity in the HIV-1 diversity, specific geographic localization of Turkey may assist in explaining this phenomenon. Extraodinary mass…”
Section: Discussionmentioning
confidence: 99%
“…11 Only a limited number of studies demonstrate that recently diagnosed HIV-1-infected Turkish patients, also transmitted drug resistance mutation (TDRM); the prevalence range was between 6.2 and 10.1%. 12,13 INSTIs are available to be prescribed in Turkey, although there is no available data on the pre-existing or transmitted INSTI resistance mutations in HIV-1-infected Turkish patients.…”
Section: Introductionmentioning
confidence: 99%
“…HIV'ın genetik değişkenliği, enfeksiyonun tanısından başlayıp tedaviye direnç oluşumuna kadar enfeksiyonun yönetimini pek çok aşamada zorlaştırmaktadır. Bulaşmada ve hastalığın progresyonunda HIV alt tipleri arasında farklılıklar olduğu belirtilmektedir (20)(21)(22).…”
Section: Tarihçeunclassified
“…Özellikle ilaç gruplarında ortaya çıkan direnç oranları ampirik tedaviyi belirlemede önemlidir. Hastaların çevre ülkelerle ilişkili olabildiği bu hastalıkta o ülkelere ait direnç modelleri de zaman zaman dikkat çekici boyutlara ulaşabilmektedir (20,22). HIV enfeksiyonu; multi disipliner yaklaşım, erken tanı, düzenli izlem ve anti retroviral tedavi ile günümüzde yönetilebilir kronik bir enfeksiyondur.…”
Section: Tedaviunclassified
“…In a single large -scale study, Sayan et al, analyzed 1306 HIV -positive patients and coinfection of HIV/HBV was 2.7%. Sexual contact was reported as the acquisition route in 98.6% of the patients, whereas the use of injection drug was only 0.3% (44). Amiri et al, reported the coinfection of HBV/HIV as 1.8% and concluded that the use of injection drug severely affected the degree of coinfection (45).…”
mentioning
confidence: 99%